Educational needs of students and teachers about the phenomenon of school violence - López Navarro, Laura (2016)
Introduction: Professional Nursing promotes the growth and development of individuals through health promotion and disease prevention through education in health problems, such as the phenomenon of school violence. This article aims to interpret the phenomenon of school violence on teachers and students in fourth and fifth grade of a public school in San Rafael Arriba de Desamparados, 2014.Method: A descriptive qualitative approach that allows the implementation of different data collection techniques in order to establish, through triangulation, the needs that affect social reality.Results: Among the main findings identified the difficulty to establish proper channels of communication between teachers and students; lack of personal skills to develop actions for the identification and containment on the subject of school violence. Both populations stressed the importance of the family as a pillar in the development of the individual and in obtaining limits, values, and assertively to function in society communication and build a culture of peace.Conclusion: School violence is a public health problem, therefore, the approach from the Pediatric Nursing should continue, as it provides knowledge and skills to plan and implement preventive programs in participating populations.